Trajectories escaping to infinity in finite time - Langley, James (American Mathematical Society, 2017)
Given a function which is transcendental and meromorphic in the plane, such that either the function has finitely many poles or its inverse function has a logarithmic singularity over infinity, the corresponding meromorphic flow has infinitely many trajectories tending to infinity in finite increasing time.